2015
DOI: 10.1186/s12883-015-0323-3
|View full text |Cite
|
Sign up to set email alerts
|

Apathy and suicide-related ideation 3 months after stroke: a cross-sectional study

Abstract: BackgroundBoth apathy and suicide are common in poststroke patients. However, the association between poststroke apathy and suicide-related ideation (SI) in Chinese stroke patients is not clear and poorly understood. The aim of this study was to examine the association between apathy and SI in stroke.MethodsA cross-sectional study was conducted to investigate the association in 518 stroke survivors from Acute Stroke Unit of the Prince of Wales Hospital in Hong Kong. Geriatric Mental State Examination-Version A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Deductively, this manifestation of depression was probably because they were lonely. Studies disclose that depression is common among stroke survivors as a result of social, cognitive, and physical dysfunction decreasing the quality of life of affected persons ( 33 - 35 ). The direct link between physical impairment and depression probably explains why those participants, in this current study who showed signs of depression, also showed signs of frustration.…”
Section: Discussionmentioning
confidence: 99%
“…Deductively, this manifestation of depression was probably because they were lonely. Studies disclose that depression is common among stroke survivors as a result of social, cognitive, and physical dysfunction decreasing the quality of life of affected persons ( 33 - 35 ). The direct link between physical impairment and depression probably explains why those participants, in this current study who showed signs of depression, also showed signs of frustration.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Apathy is also associated with suicidal ideation independently of depression three months after stroke. 32 This suggests that apathy can not only occur in tandem with depression but also exacerbate it.…”
Section: Effects Of Apathy On Functional Outcomesmentioning
confidence: 99%
“…The pharmacological treatment suggests a daily dose of nefiracetam-900 mg given for 4 weeks or cilostazol for 6 months helps in reducing symptoms of apathy in post-stroke depression. The non-pharmacological treatment such as problem-solving therapy, motivational therapy, milieu therapy, and occupational therapy showed a significant reduction in apathy after stroke [72].…”
Section: Post-stroke Apathymentioning
confidence: 97%